Automated Quantification of Mitochondrial Fragmentation in an In Vitro Parkinson's Disease Model. Issue 1 (4th November 2020) - Rees, Daniel J.; Roberts, Luke; Carla Carisi, M.; Morgan, Alwena H.; Brown, M. Rowan; Davies, Jeffrey S.
Abstract: Neuronal mitochondrial fragmentation is a phenotype exhibited in models of neurodegeneration such as Parkinson's disease. Delineating the dysfunction in mitochondrial dynamics found in diseased states can aid our understanding of underlying mechanisms of disease progression and possibly identify novel therapeutic approaches. Advances in microscopy and the availability of intuitive open‐access software have accelerated the rate of image acquisition and analysis, respectively. These developments allow routine biology researchers to rapidly turn hypotheses into results. In this protocol, we describe the utilization of cell culture techniques, high‐content imaging (HCI), and the subsequent open‐source image analysis pipeline for the quantification of mitochondrial fragmentation in the context of a rotenone‐based in vitro Parkinson's disease model. © 2020 The Authors. Basic Protocol 1 : SN4741 neuron culture and treatment in a rotenone‐based model of Parkinson's disease Basic Protocol 2 : Identification of cell nuclei, measurement of mitochondrial membrane potential, and measurement of mitochondrial fragmentation in mouse‐derived midbrain dopaminergic neurons